Institutions as key drivers of collective action in WUAs [Water User Associations] of Uzbekistan - Mochalova, Elizaveta; Anarbekov, Oyture; Kahhorov, U. (2014)
This paper presents a multifactor approach for performance assessment of Water Users Associations (WUAs) in Uzbekistan in order to identify the drivers for improved and efficient performance of WUAs. The study was carried out in the Fergana Valley where the WUAs were created along the South Fergana Main Canal during the last 10 years. The farmers and the employees of 20 WUAs were questioned about the WUAs’ activities and the quantitative and qualitative data were obtained. This became a base for the calculation of 36 indicators divided into 6 groups: Water supply, technical conditions, economic conditions, social and cultural conditions, organizational conditions and information conditions. All the indicators assessed with a differentiated point system adjusted for subjectivity of several of them give the total maximal result for the associations of 250 point. The WUAs of the Fergana Valley showed the score between 145 and 219 points, what reflects a highly diverse level of the WUAs performance in the region. The analysis of the indicators revealed that the key points of the WUA’s success are the organizational and institutional conditions including the participatory factors and awareness of both the farmers and employees about the work of WUA. The research showed that the low performance of the WUAs is always explained by the low technical and economic conditions along with weak organization and information dissemination conditions. It is clear that it is complicated to improve technical and economic conditions immediately because they are cost-based and cost-induced. However, it is possible to improve the organizational conditions and to strengthen the institutional basis via formal and information institutions which will gradually lead to improvement of economic and technical conditions of WUAs. Farmers should be involved into the WUA Governance and into the process of making common decisions and solving common problems together via proper institutions. Their awareness can also be improved by leading additional trainings for increasing farmers’ agronomic and irrigation knowledge, teaching them water saving technologies and acquainting them with the use of water measuring equipment so it can bring reliable water supply, transparent budgeting and adequate as well as equitable water allocation to the water users.